2005
DOI: 10.1002/eji.200425926
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Th1 responses in mice deficient in Epstein‐Barr virus‐induced gene 3 and challenged with physiological doses of Leishmania major

Abstract: Protection against Leishmania major is dependent on IL‐12 release from L. major‐infected dendritic cells (DC) that induce IFN‐γ‐producing Th1/Tc1 cells. IL‐27, a novel member of the IL‐12 family, is a heterodimer composed of p28 and IL‐12p40‐related Epstein‐Barr virus‐induced gene 3 (EBI3), and was shown to be produced by DC. In this study, we utilized EBI3‐deficient mice to investigate the role of IL‐27 in leishmaniasis using physiological low‐dose infections that mimic natural transmissions. Lesions in EBI3–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 33 publications
5
38
0
3
Order By: Relevance
“…Moreover, repeated antigen challenge in lung EBI-3 -/-CD11c + cells led to increased release of IFN-c or IL-12 while IFN-a continued to be down-regulated as compared to wildtype lung CD11c + cells. This could be consistent with the findings in the L. major model in which targeted deletion of EBI-3 led to increased production of IFN-c by total cells isolated from lymph nodes [39]. Importantly, we defined here for the first time that the cells overproducing IFN-c in EBI-3-deficient mice are CD11c + and not CD4 + T cells, as they are CD3 -.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, repeated antigen challenge in lung EBI-3 -/-CD11c + cells led to increased release of IFN-c or IL-12 while IFN-a continued to be down-regulated as compared to wildtype lung CD11c + cells. This could be consistent with the findings in the L. major model in which targeted deletion of EBI-3 led to increased production of IFN-c by total cells isolated from lymph nodes [39]. Importantly, we defined here for the first time that the cells overproducing IFN-c in EBI-3-deficient mice are CD11c + and not CD4 + T cells, as they are CD3 -.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, this cytokine profile seems to be dependent on the type and amount of antigen presented to the DC. In fact, we found, similarly to data in experimental colitis [29] and in contrast to the L. major model [39], reduced production of two Th2 cytokines in EBI-3-deficient mice, as EBI-3-deficient lung CD4 + T cells produced less IL-4 and IL-5 as compared to wild-type CD4 + T cells in a murine model of asthma after OVA sensitization and challenge. Moreover, repeated antigen challenge in lung EBI-3 -/-CD11c + cells led to increased release of IFN-c or IL-12 while IFN-a continued to be down-regulated as compared to wildtype lung CD11c + cells.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our current study indicates that EBI3 may play different role in the immunity to L. major and L. monocytogenes. Zahn et al [18] reported that EBI3-deficient mice showed impaired Th1 response and impaired protection to Leishmania major at the early stage when mice were challenged with low doses of L. major. However, at the late stage of infection, enhanced Th1 cytokine IFN-c and reduced Th2 cytokine IL-4 production were observed.…”
Section: Discussionmentioning
confidence: 99%
“…EBI3-deficient mice exhibit disrupted Th2 responses likely due to altered invariant natural killer T cell function [17]. However, impaired Th1 responses to Leishmania major in EBI3-deficient mice were also reported [18]. More recently, EBI3-deficient mice were reported to display enhanced neutrophil migration and oxidative burst capacity in a murine model of peritonitis, resulting in enhanced bacterial clearance and local control of infection [19].…”
Section: Introductionmentioning
confidence: 99%